INDIGENOUS PEOPLES AND TRADITIONAL COMMUNITIES AND PUBLIC POLICIES IN BRAZIL - de Miranda, Evely Bocardi; Sguarezi, Sandro Benedito; Alcântara, Liliane Cristine Schlemer; Sampaio, Carlos Alberto Cioce (Seven Editora, 2025)
The National Policy for the Sustainable Development of Traditional Peoples and Communities (PNPCT), established by Decree No. 6,040/2007, is recognized as a historical and legal milestone in the search for a balance between human relations and the environment. This recognition stems, above all, from valuing culturally differentiated groups and encouraging the sustainable use of biodiversity. However, the invisibility of these groups has resulted in the weakening or loss of knowledge, ancestry, and belonging, in addition to compromising the conservation of biodiversity due to the absence of adequate public policies. Given this scenario, it is essential to foster debates that promote the legitimacy of the PNPCT and the appreciation of the traditional practices and knowledge of Native Peoples and Traditional Communities, which play a fundamental role in the socio-environmental balance. The present work aims to understand the importance of government public policies aimed at Native Peoples and Traditional Communities, highlighting their interrelationship with Good Living as a means to preserve culture, heritage, traditional knowledge and biodiversity. The research, of a bibliographic nature and with an interdisciplinary focus, highlights the indispensability of systematized public policies directed to Native Peoples and Traditional Communities. In this context, the PNPCT must prioritize socio-cultural development, the appreciation of traditional knowledge and knowledge, and respect for the identity of these groups, reaffirming their essential role in building a sustainable and inclusive future. DOI: https://doi.org/10.56238/sevened2024.037-185